Shifting from State-Centric to Human-Based Security and Foreign Policy: A Conflict Management Technique in Nigeria? - Ugwu, Obinna Christian; Ohabuenyi, Jonas; Nnamani, Kelechi Elijah (Universitas Islam Indonesia, 2023)
This study examined the efficacy of human-centered foreign and security policies in the management of insecurity in Nigeria. This highlights the limitations inherent to the dominant state-centric security mechanism in Nigeria. The study argues that the proliferation of traditional threats manifesting in the Boko Haram insurgency, Biafra separatist agitation, Niger Delta militancy, and Fulani herdsmen uprising were attributed mainly to the government’s disregard for socioeconomic gaps and political contexts that predispose people to aggressive behavior. Instead of addressing waves of insecurity, military operations complicate and widen their scope. The study, therefore, calls for a review of the existing security architecture and foreign policy objectives of the state in line with the principles of human security. Understanding the context of fueling and sustaining insecurity as well as evolving appropriate human-centric security and foreign policy measures are key to managing violent conflicts in Nigeria. Most importantly, appropriate constitutional provisions relating to human security should be strictly implemented, while professionals should be properly engaged in the task of developing and implementing foreign security policies in Nigeria.